Clinicopathological and Preclinical Patient-Derived Model Studies Define High Expression of NRN1 as a Diagnostic and Therapeutic Target for Clear Cell Renal Cell Carcinoma - Kamada, Shuhei; Ikeda, Kazuhiro; Suzuki, Takashi; Sato, Wataru; Kitayama, Sachi; Kawakami, Satoru; Ichikawa, Tomohiko; Horie, Kuniko; Inoue, Satoshi (Frontiers in Oncology, 2021)
Background: Acquired therapeutic resistance and metastasis/recurrence remain significant challenge in advance renal cell carcinoma (RCC), thus the establishment of patient-derived cancer models may provide a clue to assess the problem. We recently characterized that neuritogenesis-related protein neuritin 1 (NRN1) functions as an oncogene in testicular germ cell tumor. This study aims to elucidate the role of NRN1 in RCC. Methods: NRN1 expression in clinical RCC specimens was analyzed based on immunohistochemistry. NRN1-associated genes in RCC were screened by the RNA-sequencing dataset from The Cancer Genome Atlas (TCGA). RCC patient-derived cancer cell (RCC-PDC) spheroid cultures were established and their viabilities were evaluated under the condition of gene silencing/overexpression. The therapeutic effect of NRN1-specific siRNA was evaluated in RCC-PDC xenograft models. Results: NRN1 immunoreactivity was positively associated with shorter overall survival in RCC patients. In TCGA RCC RNA-sequencing dataset, C-X-C chemokine receptor type 4 (CXCR4), a prognostic and stemness-related factor in RCC, is a gene whose expression is substantially correlated with NRN1 expression. Gain- and loss-of-function studies in RCC-PDC spheroid cultures revealed that NRN1 significantly promotes cell viability along with the upregulation of CXCR4. The NRN1-specific siRNA injection significantly suppressed the proliferation of RCC-PDC-derived xenograft tumors, in which CXCR4 expression is significantly repressed. Conclusion: NRN1 can be a potential diagnostic and therapeutic target in RCC as analyzed by preclinical patient-derived cancer models and clinicopathological studies.